2012
DOI: 10.1186/1749-8546-7-5
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Chinese herbal medicine in treating liver fibrosis: a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundThe studies on the effectiveness of Chinese herbal medicines (CHM) in treating liver fibrosis (LF) were not consistent. This study aims to systematically review the effectiveness of CHM on treating LF patients.MethodsDatabases including MEDLINE, AMED, EMBASE, The Cochrane Central Register of Controlled Trials, China National Knowledge Infrastructure, TCMOnline, Chinese Biomedical Literature Database, and Chinese Medical Current Contents were searched up to March 2011. Randomized controlled trials (RC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Since liver is an essential organ for detoxification and metabolism, and all pharmaceuticals make their way to the liver, for storage and therefore it is more prone to damage [ 127 , 128 ]. Paracetamol is widely used to relieve pain and reduce fever.…”
Section: Antioxidants For Prevention and Treatment Of Liver Diseasmentioning
confidence: 99%
“…Since liver is an essential organ for detoxification and metabolism, and all pharmaceuticals make their way to the liver, for storage and therefore it is more prone to damage [ 127 , 128 ]. Paracetamol is widely used to relieve pain and reduce fever.…”
Section: Antioxidants For Prevention and Treatment Of Liver Diseasmentioning
confidence: 99%
“…The reviewers indicated that the common CHM formulas, including Fufang Biejia Ruangan, Decoction of Radix Salviae Milltorrhizae, Radix Astragali and Rhubarb, or Anluo Huaxian Pills, were as efficacious as conventional anti-cirrhosis drugs but with fewer reported adverse effects. However, the low quality of many of the trials puts these conclusions into question [8].…”
Section: Introductionmentioning
confidence: 99%
“…Medicinal plants and their derivatives contain a wide variety of bioactive phytochemicals with a diverse pharmacological spectrum [ 10 , 11 ]. Essential oils constituents including terpenes, terpenoids, phenylpropenes, and other degradation products have been reported to exhibit strong antioxidant and anti-inflammatory activities [ 12 ].…”
Section: Introductionmentioning
confidence: 99%